2018
DOI: 10.1177/2380084417749215
|View full text |Cite
|
Sign up to set email alerts
|

Free Sugars Consumption around Bedtime and Dental Caries in Children: A Systematic Review

Abstract: This systematic review aimed to assess the association between food and drink consumption around bedtime-specifically, food and drinks containing free sugars-and the risk of dental caries in children. Five electronic databases were searched (PubMed, Ovid Medline, EMBASE, Web of Science, and Scopus) to identify studies that investigated any relationship between food and drink around bedtime and dental caries in 3-to 16-y-old children. The Agency for Healthcare Research and Quality domain guidelines were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…Despite the low quality of evidence, they found a positive association between dental caries and free sugar consumption at bedtime in children. This systematic review emphasized on more consistent evidence for preschool children compared with older groups [26]. Tagi et al, in 2018 showed that children who consumed cariogenic food or drinks between main meals (p=0.01) and within two hours before bedtime (p=0.04) had significantly higher mean caries as measured according to the D4-6MFT index compared with children who did not have this habit [27].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low quality of evidence, they found a positive association between dental caries and free sugar consumption at bedtime in children. This systematic review emphasized on more consistent evidence for preschool children compared with older groups [26]. Tagi et al, in 2018 showed that children who consumed cariogenic food or drinks between main meals (p=0.01) and within two hours before bedtime (p=0.04) had significantly higher mean caries as measured according to the D4-6MFT index compared with children who did not have this habit [27].…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be a sensible approach, particularly for age ranges where other key food sources such as RTEBC and sweetened dairy products still contribute significantly to overall nutrient intake. A recent systematic review investigating the association between consumption of food and drink containing FS close to bedtime and the risk of dental caries in children concluded that while there was a positive association, the quality of the evidence was very low [52]. However, the evidence supporting current recommendations to restrict bedtime consumption of food and drink containing FS was more consistent for preschool children than for older groups.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, evidence has shown that the oral health practices of parents' influence their children's dental status [30]. Potentially, this may signify that there is a crucial need to motivate parents and schoolchildren to adhere to sound oral health practices and lifestyles, particularly about controlling sugar consumption prior to and at bedtime, and using fluoride toothpaste [30,31].…”
Section: Advances In Dentistry and Oral Health Discussionmentioning
confidence: 99%